2023
DOI: 10.30935/ejsee/13776
|View full text |Cite
|
Sign up to set email alerts
|

Alternative ideas about concepts of physics, a timelessly valuable tool for physics education

Konstantinos T. Kotsis

Abstract: Alternative ideas, defined as faulty or incomplete understandings of scientific concepts, are prevalent among students across all age groups and educational levels. In physics, misconceptions often arise from everyday experiences, intuitive reasoning, and oversimplified analogies. The persistence of misconceptions in students’ understanding of physics concepts can hinder learning and compromise scientific literacy. Consequently, research on alternative ideas has emerged as a critical aspect of science educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 155 publications
0
0
0
Order By: Relevance
“…The advantage is that the teacher, knowing the students' misconceptions, uses appropriate teaching strategies to build science knowledge (Driver et al, 1985). Unfortunately, have been reported that students and primary education teachers have the same misconceptions about science concepts and phenomena (Kotsis, 2023). The same has been reported for the Pre-service teachers (Gavrilas & Kotsis, (2023); Stylos et al, 2023), making the problem very important.…”
Section: Teachers and Students Have The Same Misconceptionsmentioning
confidence: 83%
See 1 more Smart Citation
“…The advantage is that the teacher, knowing the students' misconceptions, uses appropriate teaching strategies to build science knowledge (Driver et al, 1985). Unfortunately, have been reported that students and primary education teachers have the same misconceptions about science concepts and phenomena (Kotsis, 2023). The same has been reported for the Pre-service teachers (Gavrilas & Kotsis, (2023); Stylos et al, 2023), making the problem very important.…”
Section: Teachers and Students Have The Same Misconceptionsmentioning
confidence: 83%
“…The important role of misconceptions in science teaching is well known (Kotsis, 2023). Misconceptions about a science concept can have profound implications on the learning process, influencing the trajectory of how human beings acquire knowledge.…”
Section: Teachers and Students Have The Same Misconceptionsmentioning
confidence: 99%
“…Educators should possess the appropriate knowledge and a friendly attitude toward the environment to teach and sensitize their students (Gontas et al, 2020;Oncu & Unluer, 2015;Papanikolaou et al, 2023). Educators can enhance students' environmental awareness only when they have fundamental ecological knowledge and the right experience to achieve specific educational objectives (Desjean-Perrotta et al, 2008;Kotsis, 2023;Vlachos et al, 2024). Moreover, educators must teach environmental topics from the early years of students' lives.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…However, many students struggle to connect these abstract ideas with real-life experiences, lacking engagement and understanding (Kaye & Ogle, 2022). Students have many misconceptions about physics concepts (Resbiantoro & Setiani, 2022) and cannot apply the sciences in real life (Kotsis, 2023). The fact is that misconceptions also have adults, especially persons involved with education as Pre-Service Teachers (Gavrilas & Kotsis, 2023;Stefanou et al, 2023) and University Physics Department Students (Stylos et al, 2008;Migdanalevros & Kotsis, 2021;.…”
Section: Introductionmentioning
confidence: 99%